Black seed oil inhibits the migration of triple‐negative breast cancer cells and regulates MMP‐9 expression - Ghina Lintangsari; Alma Nuril Aliyah; Gergorius Gena Maran; Adam Hermawan; Edy Meiyanto (Indonesian Journal of Biotechnology, 2025)
Black seed (Nigella sativa L.) is well known for its pharmacological properties, particularly its anticancer activity, with previous studies demonstrating its cytotoxic effects on several cell lines, such as A‐549, DLD‐1, MDA‐MB231, or HCT. This study aims to investigate the effects of black seed oil (BSO) on the migratory activity of 4T1 triple‐negative breast cancer (TNBC) cells, focusing on its bioactive properties. BSO was extracted via hydro‐distillation and analyzed for its phytochemical composition using gas chromatography–mass spectrometry (GC‐MS). The cytotoxicity of BSO and doxorubicin (Dox) was assessed using the MTT assay. The effects of BSO and Dox on cell migration and matrix metalloproteinase‐9 (MMP‐9) expression were evaluated using a scratch wound‐healing assay and gelatin zymography method respectively. Additionally, intracellular reactive oxygen species (ROS) levels were measured using 2’,7’‐dichlorofluorescin diacetate (DCFDA) staining. GC‐MS analysis identified p‐cymene as a major component of BSO, along with various other bioactive compounds. BSO exhibited low toxicity toward 4T1 cells, while its combination with Dox reduced cell viability in a dose‐dependent manner. Furthermore, BSO in combination with Dox inhibited cell migration and suppressed MMP‐9 expressions in 4T1 cells. BSO treatment also led to an increase in ROS levels. In conclusion, BSO exhibits potential anticancer properties by inhibiting cell migration and downregulating MMP‐9 expression, highlighting its possible therapeutic role in TNBC treatment.